Social -Cultural factors affecting family stability:A case of Mukono Municipality - Asaph Barigye (Uganda Christian University, 2024)
The study investigates social cultural factors influencing family stability in Mukono Municipality, focusing on key factors such as educational differences, poverty, alcoholism, and childlessness. Family instability, marked by divorce, separation, and relationship turmoil, has become a growing concern globally and in Mukono Municipality, leading to adverse effects on children's mental and physical health. The research aims to identify the major social cultural factors that contribute to this instability and provide viable solutions to address them. Conducted within Mukono Municipality , the study's scope includes examining the impact of social cultural dynamics on family stability, while acknowledging limitations in generalizing findings due to the study’s localized focus. The research findings will contribute to policymaking and academic discourse on family stability, offering a foundation for future investigations and interventions.This study explores the social cultural factors affecting family stability, particularly in Mukono Municipality. Family instability, characterized by events such as divorce, separation, and partner changes, has seen a rapid increase globally and locally. It often results in negative consequences for children, including emotional distress, neglect, and behavioral issues. The research focuses on understanding the social cultural factors such as differences in educational attainment, economic disparities, alcoholism, and childlessness that contribute to family instability in Mukono Municipality, especially among married couples aged 18 to 32. The study was conducted in Mukono Municipality and seeks to identify key social cultural dynamics that threaten family cohesion. The investigation highlights the consequences of family instability, including mental health challenges, domestic violence, and social deviance among children. Furthermore, it examines possible solutions to these social cultural challenges in an effort to foster family stability. While previous approaches have emphasized legal and psychological interventions, this study adopts a social cultural-centric perspective to fill gaps in existing research. The findings are expected to offer practical solutions for policymakers, NGOs, and academics, guiding future interventions to mitigate family instability. However, the research acknowledges limitations in generalizing results due to the focused scope of the study. The theoretical framework suggests that social cultural factors are the primary determinants of family stability, with outcomes influenced by external variables like societal norms and support systems.